MEMAHAMI LEBIH LANJUT PENERAPAN STRATEGI ANTI FRAUD BAGI BANK UMUM DI INDONESIA - Ciptaningsih Tri (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This article will discuss about the new Bank Indonesia Regulation Number 13/28/DPPNP. This regulation contains about Anti-Fraud policy that to be set for commercial banks in Indonesia. The discussion includes a discussion of the rules related to the strategies that will be applied to the implementation of the Regulation of Bank Indonesia as well as examples of the application of Anti-Fraud policy that existing in other countries to be used as comparative data. The purpose of this article is to provide a better understanding of this rule, so in this article will more talking about the form of exposure rule and its other issues related to this topic. Key words: Anti Fraud Policy